RESCUED CHILEAN MINERS GREETED AS HEROES BUT THEY’RE ALSO VICTIMS - Aigner, Mike; Brook, Stony (La Sociología en sus Escenarios, 2010)
Abstract. Many in the international labor movement have complained that news accounts have ignored the poor treatment of workers by the mining company. It's important to note that working conditions in Chile are notoriously unsafe. There were more than 191,000 workplace accidents, including 443 deaths, in a country with only a population of 17 million people in 2009, an astronomical rate for such a small country. Resumen. La tragedia minera de los 33 mineros atrapados hizó publica la difícil situación laboral y social de miles de mineros que trabajan en el inhóspito desierto de Atacama de Chile. El milagro minero sólo cubre a las grandes empresas y oculta la real situación laboral y de seguridad de las decenas de minas ilegales o legales que trabajan en precarias condiciones.